Materialismo agônico: a relação entre mente e matéria na filosofia de Schopenhauer - Oliveira, André Henrique Mendes Viana de (2020)
The criticism of the concept that there would be an independent substance identified as soul (or, mind, in actual terms) can be found in Arthur Schopenhauer's thought, especially in the second volume of his main work, The World as Will and Representation, where the philosopher deepens his theses about the relation between our brain functions and our volitional nature. Starting from this criticism, our proposal was to clarify the epistemological assumptions of the schopenhaurean philosophy, as well as circumscribe in its transcendental idealism his theses on the relation between body and mind in order, as a specific objective, to clarify the tension between intellect (mind) and will from the schopenhauerian notion of the brain, and, as a broader scope, characterize the distinction between the physical and the metaphysical from the notions of intellect and will. We have thus traced a course that has led us to address the issues surrounding the epistemology, psychology, and metaphysics of the german thinker. We hold that the old dualism mind (immaterial) - body (material) reappears in his philosophy as a tense transition between will (in principle, immaterial) and mind/body (material). Our hypothesis is that Schopenhauer's thesis should presuppose the materiality of the will (at least in its psychological dimension) as a constituent element of the brain, which would certainly imply a reconsideration of that concept, that is, of the will, as a metaphysical notion. We believe that there is in Schopenhauer's philosophical system a type of non-reductionist materialism, in which matter presents an essentially conflicting quality and goes beyond the limits of the language of the natural sciences: an agonizing materialism that constitutes the whole nature and is reflected in the permanent conflict between intellect and will. Our purpose is that such an investigation focused on this issue can contribute not only as an update of the schopenhauerian epistemology, since the investigation inserts it into a current debate, but also can provide notes for a possible philosophy of mind in the transition to contemporaneity